Prostate cancer detection with transrectal in-bore MRI biopsies: impact of prostate volume and lesion features - Alexander Schaudinn; Harald Busse; Constantin Ehrengut; Nicolas Linder; Jonna Ludwig; Toni Franz; Lars-Christian Horn; Jens-Uwe Stolzenburg; Timm Denecke (Insights into Imaging)
Abstract Objectives To systematically analyze the diagnostic outcome of transrectal in-bore MRI-guided biopsies as a function of prostate volume and lesion features. Methods This single-center study retrospectively included 184 consecutive patients with transrectal in-bore MRI biopsies and histological analysis after multiparametric MRI diagnostics of at least one PI-RADS ≥ 3 lesion. Diagnostic and biopsy MRI data were analyzed for a number of patient and imaging features, specifically prostate volume, lesion size, lesion location (longitudinal, sagittal and segmental) and lesion depth. Features were then compared for statistically significant differences in the cancer detection rate (CDR) of clinically significant (cs-PCa) and any prostate cancer (any-PCa) using categorical and continuous variables. Results A total of 201 lesions were biopsied detecting cs-PCa in 26% and any-PCa in 68%, respectively. In subgroup analyses of all features, the CDR of cs-PCa differed significantly between ranges of lesion size only (p < 0.001, largest for large lesions). In multivariable analysis, however, only PI-RADS score and PSA showed a significant association with a higher risk of cs-PCa. Conclusions The cancer detection rates of transrectal in-bore MRI-guided biopsies did not vary significantly for prostate volume, lesion size or lesion location. This suggests that the diagnostic performance of such an approach is not necessarily compromised for challenging biopsy settings like large glands, small lesions or eccentric locations. A translation of these findings to other cohorts might be limited by the low detection rate for clinically significant cancer. Critical relevance statement This systematic analysis indicates that the diagnostic performance of transrectal in-bore biopsies might not be substantially impaired by patient-specific factors like prostate volume, lesion size, and lesion location, making it a viable option for challenging biopsy cases as well. Key Points The impact of prostate and lesion features on in-bore MRI biopsy performance is controversial. Neither prostate volume, lesion size, nor location showed significant impact on cancer detection. In-bore biopsy does not seem to be limited by challenging sampling geometries. Graphical Abstract